Draft Evener - Sleight, Milton W. (United States. Patent Office., 1902)
Patent for invention that "relates to four-horse draft equalizers, and is well adapted for use on plows-- gang-plows, sulky-plows, and grain-plows-- and may be used also on wagons and other vehicles drawn by horse-power" (lines 8-12). Illustrations are included